Very High Resolution Tools for the Monitoring and Assessment of Environmental Hazards in Coastal Areas - García-Sánchez, Guillermo; Mancho, Ana M.; Ramos, Antonio G.; Coca, Josep; Pérez-Gómez, Begoña; Álvarez-Fanjul, Enrique; Sotillo, Marcos G.; García-León, Manuel; García-Garrido, Víctor J.; Wiggins, Stephen (Frontiers in Marine Science, 2021)
Recently, new steps have been taken for the development of operational applications in coastal areas which require very high resolutions both in modelling and remote sensing products. In this context, this work describes a complete monitoring of an oil spill: we discuss the performance of high resolution hydrodynamic models in the area of Gran Canaria and their ability for describing the evolution of a real-time event of a diesel fuel spill, well documented by port authorities and tracked with very high resolution remote sensing products. Complementary information supplied by different sources enhances the description of the event and supports their validation.